2017
DOI: 10.1097/gme.0000000000000919
|View full text |Cite
|
Sign up to set email alerts
|

The association of surgical versus natural menopause with future left ventricular structure and function: The Coronary Artery Risk Development in Young Adults (CARDIA) Study

Abstract: OBJECTIVE Evaluate the association between surgical (SM) versus natural menopause (NM) in relation to later left ventricular (LV) structure and function, while taking into account the LV parameters and other cardiovascular disease risk factor (CVDRF) levels that predates the menopausal transition. METHODS We studied 825 premenopausal women from the CARDIA study in 1990–1991 (baseline, mean age: 32 years) who later reached menopause by 2010–2011 and had echocardiograms at these two time points. RESULTS Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
(38 reference statements)
2
11
0
Order By: Relevance
“…Additionally, the study by Ying et al 15 included women who had natural or surgical menopause. As shown in a previous CARDIA study, 35 women who have surgical menopause tend to have adverse parameters of LV structure and function compared with women who reached natural menopause.…”
Section: Discussionmentioning
confidence: 65%
“…Additionally, the study by Ying et al 15 included women who had natural or surgical menopause. As shown in a previous CARDIA study, 35 women who have surgical menopause tend to have adverse parameters of LV structure and function compared with women who reached natural menopause.…”
Section: Discussionmentioning
confidence: 65%
“…In this study, the CVD risk factors were shown to be more important determinants of adverse cardiac geometry than the loss of estrogen. 35 Conventional measures of systolic function, including ejection fraction and fractional shortening, were preserved following ovariectomy in the present study. Previous models of estrogen loss by ovariectomy have also reported preserved systolic function.…”
Section: Discussionmentioning
confidence: 66%
“…Consequently, we surmised that nonhormonal factors concurrently impact NT-proBNP elevation and HF development in postmenopausal women and the relative contributions of hormonal and nonhormonal factors may vary for women who have experienced natural or surgical menopause. In the Coronary Artery Risk Development in Young Adults Study, an unfavorable CVD risk profile before surgical menopause was contributory to future changes in LV structure and function 38 . In the Tehran glucose and lipid study, the cardiometabolic abnormalities seen in the postmenopausal period were influenced by the type of menopause and were more prevalent in women with surgical menopause 39 .…”
Section: Discussionmentioning
confidence: 99%
“…In the Coronary Artery Risk Development in Young Adults Study, an unfavorable CVD risk profile before surgical menopause was contributory to future changes in LV structure and function. 38 In the Tehran glucose and lipid study, the cardiometabolic abnormalities seen in the postmenopausal period were influenced by the type of menopause and were more prevalent in women with surgical menopause. 39 This evidence was countered by Matthews et al in the Study of Women's Health across the Nation where the type of menopause was not a determinant of CVD risk status either before or after the onset of menopause.…”
Section: Discussionmentioning
confidence: 99%